1970
DOI: 10.1017/s0022112070001921
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instabilities in rapidly rotating systems

Abstract: Thermal instabilities of a contained fluid are investigated for a fairly general class of problems in which the dynamics are dominated by the effects of rotation. In systems of constant depth in the direction of the axis of rotation the instability develops when the buoyancy forces suffice to overcome the stabilizing effects of thermal conduction and of viscous dissipation in the Ekman boundary layers. Owing to the Taylor–Proudman theorem, a slight gradient in depth exerts a strongly stabilizing influence. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
568
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(604 citation statements)
references
References 3 publications
30
568
0
6
Order By: Relevance
“…Figure 2 demonstrates that the decrease of the Ekman number goes along with a smaller length scale. The reason becomes apparent when considering the linear onset of convection (Roberts 1968;Busse 1970): While the main part of the Coriolis force is balanced by pressure gradients, viscous forces must balance a remaining smaller part in order to facilitate convection (Zhang and Schubert 2000). As the Ekman number is lowered, the balance can only be maintained by further decreasing the length scale in order to keep viscous effects large enough.…”
Section: Convective Flow Dynamicsmentioning
confidence: 99%
“…Figure 2 demonstrates that the decrease of the Ekman number goes along with a smaller length scale. The reason becomes apparent when considering the linear onset of convection (Roberts 1968;Busse 1970): While the main part of the Coriolis force is balanced by pressure gradients, viscous forces must balance a remaining smaller part in order to facilitate convection (Zhang and Schubert 2000). As the Ekman number is lowered, the balance can only be maintained by further decreasing the length scale in order to keep viscous effects large enough.…”
Section: Convective Flow Dynamicsmentioning
confidence: 99%
“…Another possibility is the suggestion of Ioannou and Lindzen [1994] that tides raised in a slightly stable Jovian interior by Jupiter's moon Io force the zonal winds. Busse [1970Busse [ , 1976 first suggested that a multilayered structure of columnar convection rolls might produce the zonal jets in Jupiter's atmosphere through nonlinear interactions among the rolls. Convection in the rapidly rotating Jovian interior is assuredly more temporally and spatially complex than a simple set of quasi-steady columnar convection rolls.…”
Section: Static Stabilitymentioning
confidence: 99%
“…We shall focus on the second form of convection (Roberts 1968;Busse 1970; see also Jones et al . 2000), associated with large Prandtl number.…”
Section: Spatial Temporal and Amplitude Scales With A Weak¯eldmentioning
confidence: 99%
“…In (3.3), the coe¯cients of the asymptotic laws are functions of the Prandtl number Pr. It was shown by Busse (1970), based on a local asymptotic analysis, that convection with symmetry (u r ; u ; u )(r; ; ) = (u r ; u ; u )(r; ; ); (r; ; ) = (r; ; ); (3.4) (The critical Rayleigh number Rc , the corresponding azimuthal wavenumber mc and the frequency !c of convection in a rapidly rotating spherical shell with or without the e®ect of a magnetic¯eld for ri =ro = 0:4. The parameter P is related to the form of the basic magnetic eld in the magnetoconvection problem de¯ned by (4.1).…”
Section: Spatial Temporal and Amplitude Scales With A Weak¯eldmentioning
confidence: 99%